To Compare the Onset and Duration of Sensory and Motor Block of Dexmedetomidine and Clonidine as an Adjuvant to Intrathecal Bupivacaine in Patients Undergoing total Abdominal Hysterectomy - Choudhary, Dr. Rupesh; Sharma, Dr. Rahul; Jamwal, Dr. Ankita; Drishti, Dr. Divya (Journal of Biomedical and Pharmaceutical Research, 2023)
Background: Spinal anaesthesia is commonly used in gynaecological surgeries, with Bupivacaine being the most commonly used anaesthetic. Bupivacaine, on the other hand, has a shorter duration of action. This clinical study was conducted to evaluate the behaviour of intrathecal clonidine and dexmedetomidine as an adjuvant to bupivacaine in augmenting block characteristics in patients undergoing gynaecological procedures.Methods: A prospective randomized single blind study was conducted in the Department of Anesthesia IGMC SHIMLA at Kamla Nehru state hospital.Results: The mean onset time of sensory block at T6 level was significantly more in group C and was 175.09± 68.01secand was 124.44± 20.64 sec in group D. (p=0.001).  The mean time to reach the maximum sensory height was significantly early in group D and was 18.64± 4.82 min in Group C and 13.53± 2.97 min in Group D respectively. (p=0.001).  Mean time to two segment regression of the block was significantly early in group C and was 103.58± 11.25 min in Group C and 115.24± 8.91 min In Group D respectively. (p=0.001).  Mean onset motor time in seconds (modified bromage scale ≤2)for Group C and Group D was115± 8.11 and 74.6± 14.19 respectively. Group C had notably higher onset motor time than group D (p=0.001). Mean Duration of motor blockade in minutes (modified bromage scale =6) for Group C and Group D were 273.51± 18.95 and 316.67± 21.39 respectively. The difference between the groups were statistically significant (p=0.001). Conclusion: We observed statistically significant, early onset, prolonged duration of sensory and motor block in patients where dexmeditomidine 5µg was used as an adjuvant to bupivacaine 0.5% heavy in patients undergoing total abdominal hysterectomies without any significant side effects as compared to 30 µg clonidine.Keywords: Dexmedetomidine, Clonidine, Bupivacaine, motor, sensory